Reducing the effect of total harmonics distortion of synchronous machines - Haydar Ahmad H; Aree Akram M (Zanco Journal of Pure and Applied Sciences, 2019)
Synchronous machines have a great role in power system generation and controlling, reducing harmonics have been a major concern of researchers, especially with the increasing of electronic equipment and automated controls in addition to use of nonlinear loads in power systems all of these increase additional harmonic generated. In this paper various parameters were investigated such as air gap length, rotor width, rotor diameter, (pole arc / pole pitch) in order to minimize the effect of total harmonics distortion of synchronous machine by utilizing of MATLAB program.